2005
DOI: 10.1089/jwh.2005.14.729
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Health Status Experienced by Women with Gestational Diabetes and Pregnancy-Induced Hypertensive Disorders

Abstract: Women with PIH, but not GDM, more often experience significant declines in health status from prepregnancy to postpartum than unaffected women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
59
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 25 publications
7
59
2
Order By: Relevance
“…2,4 Moreover, if women with preexisting diabetes or GDM are more likely to be diagnosed with perinatal depression because of a greater number of healthcare visits, this might explain the observed increased odds of depression among women with preexisting diabetes and GDM in the study by Kozhimannil et al 11 With respect to the lack of association between GDM and antenatal depression, our findings were similar to those of three prior smaller studies. [12][13][14] However, evidence from the Australian Carbohydrate Intolerance Study in Pregnant Women, a randomized trial of treatment of hyperglycemia in pregnancy, suggests that treatment of hyperglycemia in pregnancy may improve mood profile, 26 and if women with GDM in our study were screened for depression after beginning treatment for GDM, this could explain our null findings. Therefore, we conducted a sensitivity analysis excluding women screened for depression after 4 months of gestation.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…2,4 Moreover, if women with preexisting diabetes or GDM are more likely to be diagnosed with perinatal depression because of a greater number of healthcare visits, this might explain the observed increased odds of depression among women with preexisting diabetes and GDM in the study by Kozhimannil et al 11 With respect to the lack of association between GDM and antenatal depression, our findings were similar to those of three prior smaller studies. [12][13][14] However, evidence from the Australian Carbohydrate Intolerance Study in Pregnant Women, a randomized trial of treatment of hyperglycemia in pregnancy, suggests that treatment of hyperglycemia in pregnancy may improve mood profile, 26 and if women with GDM in our study were screened for depression after beginning treatment for GDM, this could explain our null findings. Therefore, we conducted a sensitivity analysis excluding women screened for depression after 4 months of gestation.…”
Section: Discussionmentioning
confidence: 71%
“…[11][12][13][14] Three earlier studies found that the mood profile of women with GDM did not differ significantly from that of women without diabetes in pregnancy. [12][13][14] These were relatively small studies that measured antenatal depressive symptoms rather than using diagnostic criteria for major depression.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although explanations are speculative, women may have not had optimal levels of physical activity because of the presence of multiple other barriers. Previous studies suggest that the condition of pregnancy itself may not decrease activity, 21 but the presence of young children may eventually have a detrimental effect on physical activity. 22 Therefore, incontinence may not have been a significant barrier in and of itself.…”
Section: Discussionmentioning
confidence: 98%
“…These behavioral patterns may have continued after pregnancy. In another prospective cohort study, women with hGDM had significantly poorer physical functioning before pregnancy than unaffected women before pregnancy but not after delivery (9). Studies from Australia (n ϭ 226) and Denmark (n ϭ 121) suggest that onethird or fewer women with hGDM undertake adequate physical activity after delivery (10,11), and most women with hGDM had poor diets (11).…”
mentioning
confidence: 99%